PEMENUHAN HAK KONSUMEN DALAM SENGKETA PERDATA LAHAN MEIKARTA - Patrick Winson Salim; Clayment Claudio Jap; Margareth Trisya Adefinola Naru (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The fulfillment of consumer rights in the Meikarta land civil dispute is an important issue that requires serious attention. Meikarta is a large property project in Cikarang, West Java, managed by the Lippo Group. However, the project has become controversial due to the civil dispute between the Lippo Group and consumers who have purchased land within the Meikarta project. In this context, the fulfillment of consumer rights is crucial. This research focuses on two main issues, namely: (a) How can the settlement of the Meikarta land civil dispute ensure the fulfillment of consumer rights in District Court Number 162/Pdt.G/2020/PN Ckr? (b) How does the implementation of the Consumer Protection Law ensure the fulfillment of consumer rights in the Meikarta land civil dispute? The research methodology used in this study is a juridical-normative technique, which is essentially a literature review. The research findings indicate that consumer rights were not fulfilled by Meikarta due to delays in the Meikarta development, unclear land status, non-transparent information provided, and inadequate compensation.